2021
DOI: 10.1007/s10278-021-00430-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Assessment of CT Pneumonia Analysis Prototype for Predicting Disease Severity and Patient Outcome

Abstract: To perform a multicenter assessment of the CT Pneumonia Analysis prototype for predicting disease severity and patient outcome in COVID-19 pneumonia both without and with integration of clinical information. Our IRB-approved observational study included consecutive 241 adult patients (> 18 years; 105 females; 136 males) with RT-PCR-positive COVID-19 pneumonia who underwent non-contrast chest CT at one of the two tertiary care hospitals (site A: Massachusetts General Hospital, USA; site B: Firoozgar Hospital Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that quantitative CT is comparable or superior to visual CT score in assessment of the severity of COVID-19 (28,45,46). Recently, several studies have used quantitative CT to predict clinical outcomes via AI software in patients with COVID-19 (43,47,48). Liu et al found that quantitative CT features on days 0 and 4 as well as changes from days 0 to 4 could predict the progression to severe illness in COVID-19 patients, which outperformed the acute physiology and chronic health evaluation II score, NLR, and D-Dimer (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that quantitative CT is comparable or superior to visual CT score in assessment of the severity of COVID-19 (28,45,46). Recently, several studies have used quantitative CT to predict clinical outcomes via AI software in patients with COVID-19 (43,47,48). Liu et al found that quantitative CT features on days 0 and 4 as well as changes from days 0 to 4 could predict the progression to severe illness in COVID-19 patients, which outperformed the acute physiology and chronic health evaluation II score, NLR, and D-Dimer (43).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that quantitative CT features on days 0 and 4 as well as changes from days 0 to 4 could predict the progression to severe illness in COVID-19 patients, which outperformed the acute physiology and chronic health evaluation II score, NLR, and D-Dimer (43). Homayounieh et al found that despite a high frequency of motion artifacts, quantitative features of pulmonary opacities from chest CT can help stratify patients with favorable and adverse outcomes (47). Salvatore et al demonstrated that quantification of the consolidation, emphysema, and residual healthy lung parenchyma on chest CT images were independent predictors of outcome in patients with COVID-19 pneumonia (48).…”
Section: Discussionmentioning
confidence: 99%
“…The prototype estimates: lung volume (in ml), percentage of all-attenuation opacities (POO) and their volume, percentage of high-attenuation opacities (PHO) and their volume, lung severity score (LSS – measures the extent of all-attenuation in each lobe), and mean HU and standard deviations for lung parenchyma and pulmonary opacities ( Figure 7 ). The values are given separately for both lungs combined, for each lung, and for each lobe [ 44 ]. Moreover, the prototype helps to assess COVID-19 probability, especially with conjunction with RT-PCR tests, and when there are limited resources and the crunch of time (the evidence is, however, still preliminary) [ 45 ].…”
Section: Co-rads and Rsna Automatic System Of Lung Involvementmentioning
confidence: 99%
“…Although the prototype is still not permitted in clinical use, it gives particularly important data and seems to be an interesting and important proposal for further studies [ 44 ].…”
Section: Co-rads and Rsna Automatic System Of Lung Involvementmentioning
confidence: 99%
“…Fortunately, CT has been shown to be a sensitive but only slightly less specific triaging tool that can supplement and even substitute for PCR testing where needed [1]. Even as PCR and other forms of serological testing became widely available, CT and chest radiography imaging features were shown to continue to aid both diagnosis and prognosis [2,3].…”
mentioning
confidence: 99%